Investigate the business intelligence development and improvement - Mohammad Ismail Rostaminiya; Arash Hossin Zadeh Fard (Dutch Journal of Finance and Management, 2019)
The purpose of this project is to investigate the business intelligence development and improvement in order to implement in monetary system. This research is functional in term of objective, and Descriptive survey in term of gathering information. According to the previous studies, 4 aspects and 19 indicators were identified for the development and improvement of BI. Identified aspects include management, human, financial and technical aspects. A questionnaire was developed on the basis of the model and its validity was confirmed. Data analysis shows that the performance of business intelligence system in financial and monetary system is in good condition. Management, human, technical and financial aspects are considered as strong to weak aspect of performance of the business intelligence system in the organization. At the end of the study, also measures to improve the business intelligence system to enhance the performance of this system were introduced in the organization.
Keywords: 650; business intelligence; business intelligence tools; information technology; dimensions and effective measures